A proposed general model of information behaviour. - <Barbara Niedźwiedzka (Information Research: An International Electronic Journal)
Presents a critical description of Wilson's (1996) global model of information behaviour and proposes major modification on the basis of research into information behaviour of managers, conducted in Poland. The theoretical analysis and research results suggest that Wilson's model has certain imperfections, both in its conceptual content, and in graphical presentation. The model, for example, cannot be used to describe managers' information behaviour, since managers basically are not the end users of external from organization or computerized information services, and they acquire information mainly through various intermediaries. Therefore, the model cannot be considered as a general model, applicable to every category of information users. The proposed new model encompasses the main concepts of Wilson's model, such as: person-in-context, three categories of intervening variables (individual, social and environmental), activating mechanisms, cyclic character of information behaviours, and the adoption of a multidisciplinary approach to explain them. However, the new model introduces several changes. They include: 1. identification of 'context' with the intervening variables; 2. immersion of the chain of information behaviour in the 'context', to indicate that the context variables influence behaviour at all stages of the process (identification of needs, looking for information, processing and using it); 3. stress is put on the fact that the activating mechanisms also can occur at all stages of the information acquisition process; 4. introduction of two basic strategies of looking for information: personally and/or using various intermediaries.